Development and anatomical traits of black pine on an abandoned agricultural land compared to forested areas - Kara, Ferhat; Keleş, Seray Özden; Loewenstein, Edward F. (Springer Science and Business Media LLC, 2021)
Global acreage of forested lands has increased in some countries. At least some of this increase is due to the natural conversion of abandoned agricultural lands into forests. However, little is known about how these new stands develop on abandoned agricultural lands in comparison with natural regeneration of existing forests. Specifically, knowledge of how black pine (Pinus nigra Arnold) naturally establishes and develops on abandoned agricultural lands is limited. In this study, we examined the density and growth of black pine saplings as well as some morphological and anatomical characteristics on an abandoned agricultural land (AAS). These data were compared with those observed in a naturally regenerated stand (NRS), and in a forest opening (FOS). The greatest sapling density was observed in the NRS site, while sapling growth and stem biomass were higher in AAS followed by NRS and FOS. Moreover, each study site exhibited site-specific morphological and anatomical traits in their saplings. Our findings showed that site treatments and overstory openness would both play crucial role for establishment and development of black pine.
Keywords: Agriculture; Biomass; Forests; Pinus; Environmental Monitoring; Trees; 2. Zero hunger; 15. Life on land